Crystal structure and thermoelectric properties of Sr–Mo substituted CaMnO3: a combined experimental and computational study. Issue 47 (13th November 2015) - Srivastava, D.; Azough, F.; Freer, R.; Combe, E.; Funahashi, R.; Kepaptsoglou, D. M.; Ramasse, Q. M.; Molinari, M.; Yeandel, S. R.; Baran, J. D.; Parker, S. C.
Abstract : Experimental and modelling investigation of Sr/Mo (co-)doped CaMnO3 highlighted the role of Mn 3+ and presence of domain boundaries in thermal transport and thermoelectric properties. Abstract : A combination of experimental and computational techniques has been employed to study doping effects in perovskite CaMnO3 . High quality Sr–Mo co-substituted CaMnO3 ceramics were prepared by the conventional mixed oxide route. Crystallographic data from X-ray and electron diffraction showed an orthorhombic to tetragonal symmetry change on increasing the Sr content, suggesting that Sr widens the transition temperature in CaMnO3 preventing phase transformation-cracking on cooling after sintering, enabling the fabrication of high density ceramics. Atomically resolved imaging and analysis showed a random distribution of Sr in the A-site of the perovskite structure and revealed a boundary structure of 90° rotational twin boundaries across {101}orthorhombic ; the latter are predominant phonon scattering sources to lower the thermal conductivity as suggested by molecular dynamics calculations. The effect of doping on the thermoelectric properties was evaluated. Increasing Sr substitution reduces the Seebeck coefficient but the power factor remains high due to improved densification by Sr substitution. Mo doping generates additional charge carriers due to the presence of Mn 3+ in the Mn 4+ matrix, reducing electrical resistivity. The major impact of Sr on thermoelectric behaviour is the reduction of the thermal conductivity as shown experimentally and by modelling. Strontium containing ceramics showed thermoelectric figure of merit ( ZT ) values higher than 0.1 at temperatures above 850 K. Ca0.7 Sr0.3 Mn0.96 Mo0.04 O3 ceramics exhibit enhanced properties with S 1000K = −180 μV K −1, ρ 1000K = 5 × 10 −5 Ωm, k 1000K = 1.8 W m −1 K −1 and ZT ≈ 0.11 at 1000 K.